EFFECT UTILIZATION OF HERBS INGREDIENTS ON CARCASS PERCENTAGE AND RATE (MORTALITY) OF BROILER - Gaba, Kristofel Timba (Jurnal Sains Peternakan, 2015)
This research was carried out at conducted from March 25st to April 29th 2014 in Field Laboratory of Animal Husbandry Kanjuruhan University. The purpose of this research was to find out effect of in broiler herbs ingredients on carcass percentage and rate (mortality). The material used for this research were of age 100 unsex strain MB-202P produced PT. Jafta Comfeed Indonesia Tbk. All performance data collected from the experiment were statistically analyzed by using analyzed of variance for a complete randomized design by using four streatmens, namely; (P0 = ration without herbs ingredients, P1 = ration with 10% herbs ingredients, P2 = ration with 15% herbs ingredients, P3 = ration with 20% ingredients plants). Feed and water adlibitum. Every steatment was repeated 4 times, with 5 chicks each. The result showed that herbs ingredients in broiler not have real effect (P>0,05) on carcass percentage. Carcass percentage highest in of P1, P0, P3 and P2 were 80.42%, 79.71%, 78.26% and 76.76%. Average mortality (%) of P2, P1, P0, and P3 were 10,00%, 5,00% P0 and P3 0,00% or no demise. Result analysis showed that streatment no effect (P>0.05) on mortality. It is suggested to use ingredients plants 10% from 1 liter water to improve itâs performance.Keywords:Â  Herbs Ingredients, Carcass Percentage, Mortality, Broiler